Comparison of Contact Kinematics in Posterior-Stabilized and Cruciate-Retaining Total Knee Arthroplasty at Long-Term Follow-Up - Broberg, Jordan S.; Ndoja, Silvio; MacDonald, Steven J.; Lanting, Brent A.; Teeter, Matthew G. (The Journal of arthroplasty, 2020)
There is controversy regarding the superiority of posterior-stabilizing (PS) total knee arthroplasty (TKA) and cruciate-retaining (CR) TKA. Substantial work has made comparisons between PS and CR TKA at follow-ups of less than 5 years. It was the goal of the present study to compare the kinematics at greater than 5 years postoperatively between CR and PS TKA, with a secondary goal of comparing patient function. A total of 42 knees were investigated, with equal representation in the PS and CR TKA groups. Patients underwent radiostereometric analysis imaging at 0°, 20°, 40°, 60° 80°, and 100° of flexion. Contact position, magnitude of excursion, and condylar separation on each condyle were measured. A Timed-Up-and-Go functional test was also performed by patients, with the total test time being measured. Preoperative and postoperative clinical outcome scores were also collected. There were differences in contact position on both the medial and lateral condyles at multiple angles of flexion (P < .05). There was no difference (P = .89) in medial excursion; however, PS TKA had greater lateral excursion than CR TKA (P < .01). No difference (P > .99) was found in frequency of condylar separation. PS TKA was associated with faster (P = .03) total Timed-Up-and-Go test times. There were no differences in clinical outcome scores between the groups preoperatively or postoperatively. We found kinematic and functional differences that favor PS TKA. Our results suggest posterior cruciate ligament insufficiency in CR TKA, indicating that perhaps the cam/post systems in PS TKA better maintain knee kinematics and function long term.